Management of intestinal failure in inflammatory bowel disease: small intestinal transplantation or home parenteral nutrition? - Harrison, E; Allan, P; Ramu, A; Vaidya, A; Travis, S; Lal, S (WJG Press, 2014)
Inflammatory bowel disease and Crohn's disease in particular, is a common cause of intestinal failure. Current therapeutic options include home parenteral nutrition and intestinal transplantation. For most patients, home intravenous therapy including parenteral nutrition, with a good probability of long-term survival, is the favoured choice. However, in selected patients, with specific features that may shorten survival or complicate home parenteral nutrition, intestinal transplantation presents a viable alternative. We present survival, complications, quality of life and economic considerations that currently influence individualised decision-making between home parenteral nutrition and intestinal transplantation.